Esterification of Waste Cooking Oil Using Ultrasonic: Kinetic Study - Egi Agustian; Jessica Jessica; Pudji Untoro; Anny Sulaswatty (Research Center for Chemistry - LIPI, 2018)
Waste cooking oil (WCO) have a great potential as an alternative raw material for producing biodiesel. The literatures kinetic of the esterification of WCO in the presence of phosphoric acid catalyst with ultrasonic assisted are rare and most literatures used conventional method. This study aims to determine the optimum condition and the parameters of first and second order kinetics of the WCO esterification which was assisted by ultrasonic bath. Variables that used in this study are methanol/oil mole ratio, acid catalyst concentration and reaction temperature. The highest conversion was 42.08% with methanol/oil mole ratio of 15:1, a catalyst (phosphoric acid) concentration of 9% wt and temperature of 50oC within 90 minutes. The reaction time was reduced to 3 times (minute) compare to conventional method and fatty acid reduced 42%. Kinetic parameters were calculated with assumption that the esterification was the irreversible reaction. The reaction rate constant increasing with temperature. The value of activation energy for esterification of WCO is 42.94 kJ/mol for first order reaction and 35.30 kJ/mol for second order reaction.